2018
DOI: 10.1016/j.bjm.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Klebsiella pneumoniae associated with cattle infections in southwest China using multi-locus sequence typing (MLST), antibiotic resistance and virulence-associated gene profile analysis

Abstract: Klebsiella pneumoniae is important human and animal pathogen that causes a wide spectrum of infections. In this study, isolates from cattle nasal swabs samples were identified by 16S rRNA, and to evaluate the antimicrobial susceptibility, virulence gene carrying levels, and multilocus sequence typing of K. pneumoniae isolates. 33 isolates of K. pneumoniae were isolated and identified in 213 nasal swabs samples, of which 12 were hypervirulent K. pneumoniae strains. Extended Spectrum Beta-Lactamases genes were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Klebsiella pneumoniae is a facultative anaerobic, Gram-negative, rod-shaped, non-motile encapsulated bacterium capable of fermenting glucose and lactose, which can cause infection in humans, animals, and plants [ 1 , 2 ]. K. pneumoniae were classified into classical K. pneumoniae and hypervirulent K. pneumonia (hvKp) strains based on their genotypic and phenotypic biomarkers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Klebsiella pneumoniae is a facultative anaerobic, Gram-negative, rod-shaped, non-motile encapsulated bacterium capable of fermenting glucose and lactose, which can cause infection in humans, animals, and plants [ 1 , 2 ]. K. pneumoniae were classified into classical K. pneumoniae and hypervirulent K. pneumonia (hvKp) strains based on their genotypic and phenotypic biomarkers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…K. pneumoniae is considered one of the most important pathogens in public health because they are animal-borne bacterial pathogens (zoonoses) [ 1 ]. In humans, K. pneumoniae has been associated with pneumonia, urinary tract infections, bacteremia, and liver abscess, primarily in immunocompromised hosts [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, MDR Klebsiella spp was found to be 80% (Table 1). In a study from China, high rate resistance Klebsiella spp was reported to be 93.4% [45]. Similar studies documented MDR Klebsiella spp in cattle [46,47,48,49].…”
Section: Discussionmentioning
confidence: 65%
“…K. pneumonia contamination was recorded in 32% of the street food samples examined in Malaysia [8]. This bacterium is also an issue of domestic animals that threatens livestock production as well as scourging public health since these animals could serve as a vehicle for multidrug-resistant K. pneumoniae strains [9].…”
Section: Introductionmentioning
confidence: 99%